2016
DOI: 10.1038/srep31130
|View full text |Cite
|
Sign up to set email alerts
|

Loss of ADAMTS4 reduces high fat diet-induced atherosclerosis and enhances plaque stability in ApoE−/− mice

Abstract: Atherosclerosis is a chronic inflammatory disease characterized by formation of lipid-rich plaques on the inner walls of arteries. ADAMTS4 (a disintegrin-like and metalloproteinase with thrombospondin motifs-4) is a secreted proteinase that regulates versican turnover in the arterial wall and atherosclerotic plaques. Recent reports indicated elevated ADAMTS4 level in human atherosclerotic plaques and in the plasma of acute coronary syndrome patients. Nevertheless, whether increased ADAMTS4 is a consequence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 59 publications
2
40
0
Order By: Relevance
“…The process for the oil red O staining of the mesenteric artery and aorta was based on previous reports . The mesenteric artery was carefully isolated from the intestine.…”
Section: Methodssupporting
confidence: 84%
See 1 more Smart Citation
“…The process for the oil red O staining of the mesenteric artery and aorta was based on previous reports . The mesenteric artery was carefully isolated from the intestine.…”
Section: Methodssupporting
confidence: 84%
“…22 The process for the oil red O staining of the mesenteric artery and aorta was based on previous reports. 23,24 The mesenteric artery was carefully isolated from the intestine. The aorta and isolated mesenteric artery were fixed in 10% formalin for 10 minutes.…”
Section: Histopathological and Oil Red O Stainingmentioning
confidence: 99%
“…This discrepancy may be due to inter‐species differences, particularly in relation to the period of disease development. In addition, we have recently found that the loss of ADAMTS4 resulted in the attenuation of both atherosclerotic plaque formation and the plaque stability . Our results suggest that HA tended to suppress the mRNA expression of more than one ADAMTS, implying that aggrecanase activity can be controlled by HA.…”
Section: Discussionmentioning
confidence: 55%
“…Moreover, elevated circulating levels of ADAMTS4 have been reported in patients with coronary artery disease and acute coronary syndromes (Zha et al 2010). Concurring, loss of ADAMTS4 reduced atherosclerosis and enhanced plaque stability in Apoe KO mice (Kumar et al 2016). A protective role in atherosclerosis has been ascribed to ADAMTS5 as its expression is depleted in atherosclerotic aortas, leading to the accumulation of proteoglycans such as versican and biglycan, which may favour lipid retention and macrophage accumulation (Didangelos et al 2012).…”
Section: Adamtssmentioning
confidence: 99%